Anaplastic thyroid cancer: Prognostic factors, patterns of care, and overall survival. (19th February 2016) - Glaser, Scott M.; Mandish, Steven F.; Gill, Beant S.; Balasubramani, Goundappa K.; Clump, David A.; Beriwal, Sushil
Abstract: Background: Anaplastic thyroid cancer (ATC) represents a rare, aggressive malignancy. We analyzed factors predictive for overall survival (OS) and treatment modality utilization. Methods: Using the National Cancer Data Base, we identified 3552 patients with ATC. Factors associated with surgery, high‐dose radiotherapy (RT; ≥59.4 Gy), and chemotherapy utilization were evaluated using multivariable logistic regression. From this, an inverse probability‐weighted propensity score was incorporated into multivariable Cox regression analyses for OS. Results: Numerous factors predictive for high‐dose RT, total thyroidectomy, and chemotherapy utilization are described. Factors associated with improved survival were absence of clinical or pathologic lymph node involvement, absence of metastasis, tumor size ≤6 cm, negative surgical margins, surgery, RT, and chemotherapy. On conditional landmark analysis, improved survival seen with chemotherapy and surgery other than total thyroidectomy was lost, but persisted for total thyroidectomy and high‐dose RT. Conclusion: Even after correction for selection and immortal time bias, high‐dose RT resulted in improved survival. © 2016 Wiley Periodicals, Inc. Head Neck 38 : E2083–E2090, 2016